Analysis of Brand Awareness on Purchase Intention in Jelly and Pudding Powder Products with Jelly Seven Brands - Winarsih; Martono, Sri (LPPM Universitas An Nuur, 2021)
Background: Dessert is always awaited when there is an important event such as dinner with family or friends. Dessert menus are very varied, one of which is pudding and jelly. In line with the increasing consumer awareness of a brand, helping in purchasing decisions becomes a challenge and a demand for every organization that runs a business. When consumers want to buy a product, the brand name is the first thing they think of at the same time that reflects that a product has a higher brand awareness. Purpose: The purpose of this study is to examine more deeply about consumer buying interest in jelly seven products which is influenced by the level of product awareness and perceived quality. Methods: The research is an organized investigation. The population in this study were housewives in the Grobogan Regency area as many as 100 people. The sample in this study amounted to 50. The method of data collection in this study was using a questionnaire. Conclusion: From the results of the study, it can be concluded that brand awareness and perceived quality are antecedents in increasing purchase intention. This theory can be contributed to companies that produce jelly seven as an effort to increase people's buying interest. Suggestion: For the future agenda, it can be strengthened by moderating variables or mediating variables which are believed to be able to increase buying interest in the wider community. Keywords: Brand Awareness, Perceived Quality, Purchase Intention